You've got to crack a few eggs to make an omelette. Linguistic complexity and instruction in SLA. Issue 2 (1st November 2019) - de Graaff, Rick
Abstract : In this epilogue, I take a teaching practice and teacher education perspective on complexity in Instructed Second Language Acquisition. I take the stance that it is essential to understand if and how linguistic complexity relates to learning challenges, what the implications are for language pedagogy, and how this challenges the role of the teacher. Research shows that differences in task complexity may lead to differences in linguistic complexity in language learners' speech or writing. Different tasks (e.g. descriptive vs narrative) and different modes (oral vs written) may lead to different types and levels of complexity in language use. On the one hand, this is a challenge for language assessment, as complexity in language performance may be affected by task characteristics. On the other hand, it is an opportunity for language teaching: using a diversity of tasks, modes and text types may evoke and stretch lexically and syntactically complex language use. I maintain that it is essential for teachers to understand that it is at least as important to aim for development in complexity as it is to aim for development in accuracy. Namely, that 'errors' in language learning are part of the deal: complex tasks lead to complex language use, including lexical and syntactical errors, but they are a necessary prerequisite for language development.